Adverse outcomes of childbirth in high-risk maternity hospitals - Thais da Costa Oliveira; Tâmara Silva de Lucena; Jovânia Marques de Oliveira e Silva; Patrícia de Carvalho Nagliate; Regina Célia Sales Santos Veríssimo; Maria Lucélia da Hora Sales (Instituto Materno Infantil de Pernambuco, 2020)
Abstract Objectives: to analyze adverse outcomes in teaching maternity hospitals in Maceió, Alagoas, Brazil. Methods: a cross-sectional, retrospective and analytical study was carried out with a random sample of 480 medical records of postpartum women in 2016 using the Adverse Outcome Index: in-hospital maternal death, neonatal in-hospital death> 2500g and> 37 weeks, uterine rupture, unplanned maternal admission to intensive care unit, delivery trauma to the newborn, return to the operating room, admission to an intensive neonatal unit with >2500g and > 37 weeks for more than one day, Apgar <7 at the fifth minute, maternal hemotransfusion and fourth-degree perineal laceration. The data were analyzed using the Statistical Package for Social Sciences software version 22.0. Results: the results showed a 21% rate of adverse outcomes, at a rate of 26.4 for every 1,000 births, with a greater occurrence of neonatal intensive care admission with>2500g and>37 weeks for more than one day (52. 5%), maternal blood transfusion (20.8%) and unplanned maternal admission in intensive care (17.8%). Conclusions: the evaluation of adverse outcomes evidenced a high proportion of births with undesirable results, which allowed the analysis of the outlook of unfavorable outcomes related to safety in maternity wards through the use of indicators.